Blockchain distributed ledger technologies for biomedical and health care applications. - Tsung-Ting Kuo; Hyeon-Eui Kim; Ohno-Machado, Lucila; Kuo, Tsung-Ting; Kim, Hyeon-Eui (Journal of the American Medical Informatics Association, 2017)
Objectives: To introduce blockchain technologies, including their benefits, pitfalls, and the latest applications, to the biomedical and health care domains.Target Audience: Biomedical and health care informatics researchers who would like to learn about blockchain technologies and their applications in the biomedical/health care domains.Scope: The covered topics include: (1) introduction to the famous Bitcoin crypto-currency and the underlying blockchain technology; (2) features of blockchain; (3) review of alternative blockchain technologies; (4) emerging nonfinancial distributed ledger technologies and applications; (5) benefits of blockchain for biomedical/health care applications when compared to traditional distributed databases; (6) overview of the latest biomedical/health care applications of blockchain technologies; and (7) discussion of the potential challenges and proposed solutions of adopting blockchain technologies in biomedical/health care domains.